Multiple regression : Testing and interpreting interactions - Aiken, Leona S (Sage Publications, 1991)
Interactions between continuous predictors in multiple regression The effects of predictor scaling on coefficients of regression equations The problem of scale invariance Interpreting the regression coefficients Standardized solutions with multiplicative terms Testing and probing three-way interactions Structuring regression equations to reflect higher order relationships Post hoc probing of more complex regression equations Coefficients of simple slopes by computer Model and effect testing with higher order terms Some issues in testing lower order effects in models containing higher order terms Exploring regression equations containing higher order terms with global tests Sequential model revision of regression equations containing higher order terms: Exploratory tests Interactions between categorical and continuous variables Coding categorical variables Post hoc probing of significant interactions Reliability and statistical power Conclusion: Some contrasts between ANOVA and MR in practice Appendix A: Mathematical underpinnings Appendix B: Algorithm for identifying scale-independent terms Appendix C: SAS program for test of critical region(s)